Collaborative Principles For Better Supply Chain Practice : value creation up, down and across supply chains - McLennan, Norman K. (London : KoganPage, 2019)
Hyper competition and globalization mean that markets are changing. There is aggressive competition, shortening product life cycles, financial pressures and ever more demanding customers and consumers. Companies need to adopt new practices and new ways of thinking, so they are looking at collaboration across supply chains to become more sustainable, efficient and economical. Collaborative Principles for Better Supply Chain Practice looks at behavioural and commercial collaborative business principles and their application by means of case studies which showcase collaboration success across the private, public and 3rd sectors. Collaborative Principles for Better Supply Chain Practice covers different perspectives: the client looking down the supply chain, the suppliers looking up the supply chain and the inter-dependencies of organizations horizontally across the supply chain. The book explores operational and project-type environments in different industry sectors, which will help you think about your supply chain differently and optimize your processes to achieve supply chain excellence. Online supporting resources include a bonus chapter and web links.
Includes bibliographical references (pages 257-259) and index.
Keywords: Business logistics; Business networks; Business logistics; Business networks